2011
DOI: 10.1002/bdra.22865
|View full text |Cite
|
Sign up to set email alerts
|

Medications used to treat nausea and vomiting of pregnancy and the risk of selected birth defects

Abstract: Background Nausea and vomiting of pregnancy (NVP) occurs in up to 80% of pregnant women, yet its association with birth outcomes is not clear. Several medications are used for the treatment of NVP; however, data are limited on their possible associations with birth defects. Methods Using data from the National Birth Defects Prevention Study (NBDPS), a multi-site population-based case-control study, we examined whether NVP or its treatment was associated with the most common non-cardiac defects in the NBDPS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
4
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 33 publications
5
133
4
6
Order By: Relevance
“…However, this sample size ruled out only a five-fold increased risk of major malformations and not any specific malformation. Moreover, the lack of other similar cohort studies precluded conducting a meta-analysis to increase the sample size (16). Besides, no previous reports were available on toxicity or teratogenicity of vitamin B6 during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, this sample size ruled out only a five-fold increased risk of major malformations and not any specific malformation. Moreover, the lack of other similar cohort studies precluded conducting a meta-analysis to increase the sample size (16). Besides, no previous reports were available on toxicity or teratogenicity of vitamin B6 during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…One recent case-control study reported an increased risk of cleft palate (adjusted OR 2.37, 95% CI 1.18 to 4.76). 144 However, another Danish study, involving over 600,000 pregnancies, found no association with any adverse fetal outcomes. 145 Concerns have been raised regarding the risk of cardiac arrhythmias [time between start of the Q wave and of the T wave in the heart's electrical cycle (QT) prolongation] with large doses of i.v.…”
Section: Serotonin Receptor Antagonists (Ondansetron)mentioning
confidence: 95%
“…The first, in 2012, was a review of data from the National Birth Defects Prevention Study in the United States (16). A total of 4524 cases and 5859 controls were examined, and the authors looked specifically at 3 birth defect categories: orofacial clefts, neural tube defects, and hypospadias.…”
Section: Larger Studiesmentioning
confidence: 99%